Gambaran Ekspresi Cluster of Differentiation 44 (CD44) Pada Meningothelial Meningioma di RSUD Provinsi Nusa Tenggara Barat - Santosa, Hilda; Nini, Cheryl; Sabariah, Sabariah; Perdana, Muhammad Astro (LPPM Universitas Mataram, 2024)
Meningiomas are mostly benign tumors that grow slowly and are very common compared to other intracranial tumors with the most frequent subtype being meningothelial meningioma. Cluster of differentiation 44 is a cell surface glycoprotein that has an important role in cellular adhesion, migration, angiogenesis, proliferation and inflammation. This study aims to examine the description of CD44 expression in meningothelial meningioma at West Nusa Tenggara Provincial Hospital. This study is a quantitative descriptive analysis research, sample 27 cases of meningothelial meningioma CD44 expression was evaluated by immunohistochemistry. Quantitative descriptive analysis to determine the percentage of the study sample. The results obtained were 19 (70.40%) age range 41-50 years. CD44 expression in meningothelial meningioma was found to be mild in 3 (11.10%), moderate expression in 5 (18.50%) and strong in 19 (70.40%). In conclusion, most of the percentages of tumor cells that were smeared were in the severe category (percentage value of more than 50 percent).